Knockdown of USF1 and USF2 drives prolonged changes in the gene expression response of M12-5B3 cells to DNA damage - Kimberly S. Bellingham-Johnstun; Lisa A. Metzger; Jennifer L. Stone; Kevin Gerrish; Pierre R. Bushel; Michael L. Sikes (PLoS ONE, 2025)
Therapeutic resistance remains a primary obstacle to curing cancer. Healthy cells exposed to genotoxic insult rapidly activate both p53-dependent and -independent non-genetic programs that pause the cell cycle and direct either DNA repair or apoptosis. Cancer cells exploit these same pathways as they respond to stresses induced by cancer therapies. In this study, we investigated a potential role for upstream stimulatory factor 1 (USF1) and USF2 in the p53-independent response of lymphoma cells to genotoxic therapy. We previously found that lymphocytes utilize the responsiveness of USF1 to double-stranded DNA breaks to coordinate T cell receptor beta (Tcrb) gene expression during V(D)J recombination. Here, microarray gene expression analysis of derivatives of the p53-deficient mouse B lymphoma cell line, M12, revealed that simultaneously depleting cells of both USF1 and USF2 altered the expression of 940 gene transcripts (>1.50-fold change, < 0.05 FDR), relative to cells expressing a scrambled control shRNA. Seven days after exposure to a single sublethal (5 Gy) dose of ionizing radiation, USF-depleted (USFKD) cells exhibited widespread and distinct transcriptional responses from those of irradiated controls (5035 and 5054 differentially expressed gene transcripts, respectively, with roughly half shared between both cell types). Gene ontology analyses revealed that USF knockdown induced numerous changes in the expression of genes critical for immune development and function while diminishing the responsiveness of genes linked to DNA damage pathways. Microarray findings were confirmed by RT-qPCR for a panel of genes responsive to USF knockdown and/or irradiation. These findings shed further light on transcriptional responses to ionizing radiation that manifest over time in transformed cells, identifying a novel p53-independent role in lymphocytic DNA damage stress responses for USF.